Global scenario of HIV/AIDS: Declining trend and moving toward cure - Ramalingam Sekar; Manoharan Mythreyee (Wolters Kluwer Medknow Publications, 2016)
People living with Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) (PLH/PLHA) are increasing worldwide (29.8 million in 2001 and 36.9 million in 2014) mainly owing to the aversion of AIDS related deaths by effective antiretroviral therapy (ART). Although the prevalence is increasing, the new HIV infections decreased from 3.4 million in 2001 to 2 million in 2014, and AIDS-related deaths were decreased from the peak of 2.4 million in 2005 to 1.2 million in 2014. Implementation of ART with wide coverage and free access, especially in low- and middle-income countries is an important reason for the decline of AIDS-related deaths. Further, it is expected that the recent understanding in the mechanisms of latent infection and importance of reservoir could help to achieve a "functional cure" from HIV infection in near future.